Successful management of passenger lymphocyte syndrome in an ABO‐compatible, nonidentical isolated bowel transplant: a case report and review of the literature. Issue 6 (28th March 2017) - Foell, Daniel; Glasmeyer, Sabina; Senninger, Norbert; Wolters, Heiner; Palmes, Daniel; Bahde, Ralf
Abstract : BACKGROUND: Passenger lymphocyte syndrome (PLS), a subtype of graft‐versus‐host disease, is a rare disorder encountered mainly in ABO‐mismatched hematopoietic stem cell transplantation and infrequently in all types of ABO‐mismatched solid organ transplantation. We here report the fifth case of PLS in small bowel transplantation (SBTx) and the first one describing the successful management of PLS in a cadaveric, isolated SBTx. CASE REPORT: A 60‐year‐old Caucasian female with blood group A D+ suffering from short bowel syndrome received a small bowel transplant from a 32‐year‐old Caucasian female with blood group O D+ (HLA mismatch 2/6). After onset of massive hemolysis on Postoperative Day 9 the positive direct and indirect antiglobulin tests showing antibodies against A1 and A2 red blood cells (RBCs) led to the diagnosis of PLS. This complication was successfully treated by transfusion of blood group O RBC transfusions, increased immunosuppression, and plasmapheresis. CONCLUSION: In the event of severe hemolysis and anemia after ABO‐mismatched SBTx, PLS should be considered. In our case successful treatment consisted of transfusion of donor‐specific RBCs, increased immunosuppression, and plasmapheresis.